2015
DOI: 10.1088/0957-4484/27/3/03lt01
|View full text |Cite
|
Sign up to set email alerts
|

Cleaved thin-film probes for scanning tunneling microscopy

Abstract: We introduce an alternative type of probe for scanning tunneling microscopy (STM). Instead of using a needle-like tip made from a piece of metallic wire, a sharp-edged cleaved insulating substrate, which is initially covered by a thin conductive film, is used. The sharp tip is formed at the intersection of the two cleaved sides. Using this approach a variety of materials for STM probes can be used, and functionalization of STM probes is possible. The working principle of different probes made of metallic (Pt, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In parallel we observed a similar resurgence of nanofabricated STM probes [19][20][21] that can be equipped with two (fixed) probes that are compatible with ultrahigh vacuum and low-temperature operation and potentially allow the integration in ultrastable single-tip STM systems currently available [21]. Advances in modern nanofabrication techniques such as focused ion beam milling and electron beam induced deposition could lead to a tip separation of a few tens of nanometers in the very near future.…”
Section: Introductionmentioning
confidence: 70%
“…In parallel we observed a similar resurgence of nanofabricated STM probes [19][20][21] that can be equipped with two (fixed) probes that are compatible with ultrahigh vacuum and low-temperature operation and potentially allow the integration in ultrastable single-tip STM systems currently available [21]. Advances in modern nanofabrication techniques such as focused ion beam milling and electron beam induced deposition could lead to a tip separation of a few tens of nanometers in the very near future.…”
Section: Introductionmentioning
confidence: 70%
“…Afterward, we formed a sharp tip by double cleaving a substrate as it was already demonstrated in our pilot study. 12 The sharp tip is formed at the intersection of propagating cleaving lines (Figure 3b,c).…”
Section: Methodsmentioning
confidence: 99%
“…The sharpness of this probe is good enough to obtain atomic resolution in STM as confirmed in our previous report. 12 We succeed to fix the FPP on a modified quartz tuning fork force sensor (Figure 2c) and utilize it also in AFM. The FPP can easily be tailored because it has planar geometry with a relatively wide and flat face.…”
Section: Introductionmentioning
confidence: 99%
“…Existing on-chip scanning probes have already contributed in several branches such as parallel AFM [23], scanning near field microscopy [24], scanning Hall probes [25,26], scanning SQUID probes [27], among others. However the development and use of integrated STM tips has been limited [28][29][30][31]. Recent proof-of-principle experi-ments have demonstrated that such single tip probes can in fact meet the stringent criteria that STM brings [29] even under ultra-high vacuum and low temperature conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…However the development and use of integrated STM tips has been limited [28][29][30][31]. Recent proof-of-principle experi-ments have demonstrated that such single tip probes can in fact meet the stringent criteria that STM brings [29] even under ultra-high vacuum and low temperature conditions [16].…”
Section: Introductionmentioning
confidence: 99%